Validity of the Dark Triad Dirty Dozen (DTDD) test-Indonesian version - Devi, Lalita; Natalya, Lina; Siaputra, Ide Bagus; Jonason, Peter Karl (HUMANITAS published by Universitas Ahmad Dahlan., 2024)
This study addresses the need for a culturally adapted and validated measurement tool for assessing Dark Triad traits in the Indonesian population. The Dark Triad, consisting of narcissism, Machiavellianism, and psychopathy, are associated with various undesirable social and behavioral outcomes worldwide. Our research objective was to validate the Dark Triad Dirty Dozen scale within the Indonesian setting, using a multi-stage methodology, including Principal Component Analysis, Confirmatory Factor Analysis, reliability testing, and invariance testing. A sample of 429 Indonesian undergraduate students (17-23 years old) completed the adapted Dark Triad Dirty Dozen Scale, revealing strong psychometric properties, including validity by confirming a three-factor structure consistent with the theoretical framework, with model fit indices meeting established criteria (RMSEA = 0.054; GFI = 0.932; AGFI = 0.890; CFI = 0.971; NFI = 0.914; TLI = 0.959) and high reliability (α ≥ 0.7). There is also measurement invariance across men and women in DTDD. In conclusion, the adapted Dark Triad Dirty Dozen Scale is a valid and reliable means to assess Dark Triad traits in Indonesia, contributing to a deeper understanding of personality traits and their implications in this unique cultural context.